Morphoanatomical and phytochemical study of seed samples marketed as Indian Nut (Aleurites moluccana) (Research, Society and Development, 2020)
The present study was carried out with the aim of confirming the identity or the occurrence of falsification of samples marketed as Indian Nut (Aleurites moluccana). This is a prospective, experimental and qualitative study, carried out with two samples marketed as Indian nut, which were compared with an original sample of napoleon hat (Thevetia peruviana). The evaluation of botanical characteristics, Kedde's phytochemical reaction to identify cardiotonic glycosides, Thin Layer Chromatography (CCD), Classical Column Chromatography (CCC) and infrared spectrometric analysis were performed. The botanical similarity of the samples was confirmed by the visualization of histological structures characteristic of the species Thevetia peruviana. Kedde's reaction was positive for all samples, indicating the presence of cardiotonic glycosides, in accordance with the result obtained for a sample of 0.25mg digoxin tablets. The evaluated seeds and the digoxin tablets also showed similarity regarding the chromatographic profile; additionally, the chromatographic fractionation of the seeds resulted in chemically equivalent fractions; fraction 6 of each sample was subjected to analysis by infrared spectrometry, showing the same spectral pattern. The results obtained confirmed that seeds commercialized as Walnut (Aleurites moluccana) were from Napoleon Hat (Thevetia peruviana). The presence of cardiotonics in the evaluated samples calls attention to the potential risk of intoxication by users. This result highlights the occurrence of the sale of counterfeit plant drugs, which shows the need for inspection, stricter quality control for plant and herbal drugs, and, mainly, pharmaceutical guidance to promote the correct use of medicinal plants.